An Improvement of Static Subtree Partitioning in Metadata Server Cluster - Tan Zhipeng; Zhou Wei; Sun Jianliang; Zhan Tian; Cui Jie (International Journal of Distributed Sensor Networks)
Efficient metadata management is a key issue in distributed file systems. Currently a single metadata server (MDS) was used to provide metadata service in many distributed file systems. As a result the MDS is likely to be the bottleneck of the system with the expanding scale. To deal with this problem, MDS cluster has been advanced. There are subtree partitioning and hashing partitioning to realize MDS cluster and so on. In view of the strengths and weaknesses of the previous methods, the paper proposes a half-dynamic subtree strategy that supports the replication of metadata, the dynamic addition and failure recovery of MDS. Finally we implement it in the open source pNFS file system and demonstrate its high performance and availability.